How Is It Between Us? Relational Ethics and Care for the World - Zigon, Jarrett (HAU Books, 2023)
A new theory of relational ethics that tackles contemporary issues. In How Is It Between Us?, Jarrett Zigon puts anthropology and phenomenological hermeneutics in conversation to develop a new theory of relational ethics. This relational ethics takes place in the between, the interaction not just between people, but all existents. Importantly, this theory is utilized as a framework for considering some of today's most pressing ethical concerns-for example, living in a condition of post-truth and worlds increasingly driven by algorithms and data extraction, various and competing calls for justice, and the ethical demands of the climate crisis. Written by one of the preeminent contributors to the anthropology of ethics, this is a ground-breaking book within that literature, developing a robust and systematic ethical theory to think through contemporary ethical problems.